2017
DOI: 10.1016/j.ebiom.2017.09.025
|View full text |Cite
|
Sign up to set email alerts
|

MET Activation and Physical Dynamics of the Metastatic Process: The Paradigm of Cancers of Unknown Primary Origin

Abstract: The molecular and cellular mechanisms which drive metastatic spread are the topic of constant debate and scientific research due to the potential implications for cancer patients' prognosis. In addition to genetics and environmental factors, mechanics of single cells and physical interaction with the surrounding environment play relevant role in defining invasive phenotype. Reconstructing the physical properties of metastatic clones may help to clarify still open issues in disease progression as well as to lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…In solid tumors, neoangiogenesis leads to an increased intra-tumoral microcirculation, tortuous micro-vessels and irregular blood flow with unstable rheology [22,23]. Pathological examinations showed that angiogenesis inhibitors normalize the tumor vasculature, reducing the oncotic pressure, and hence normalize the interstitial water content [24].…”
Section: Discussionmentioning
confidence: 99%
“…In solid tumors, neoangiogenesis leads to an increased intra-tumoral microcirculation, tortuous micro-vessels and irregular blood flow with unstable rheology [22,23]. Pathological examinations showed that angiogenesis inhibitors normalize the tumor vasculature, reducing the oncotic pressure, and hence normalize the interstitial water content [24].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells can increase their traction forces in response to increased ECM stiffness, documented by their phenotype transition, and they must also degrade ECM. Based on our findings, we presented the hypothesis that a shift in the biomechanics plays a crucial role, centered on the concept that the forces of deformation push cell dissemination [42]. Our preliminary data indicated that the plasticity exhibited by SEMA-mutated cell clones is not relying on increased deformability and adaptation to foreign environments.…”
Section: Met-driven Invasive Growth In Brain Metastases From Nsclcmentioning
confidence: 92%
“…The main and critical issue concerns the identification/confirmation of the primary site of origin of neoplastic cells, since this can effectively guide the search for "actionable" molecular targets. In other words, the detection of a mass in the lungs imposes a determination of whether it is a primary lung tumor or a lung metastatic lesion spread from a different organ of origin [29,30]. The immunophenotype expressed by cancer cells can be of help routinely in suggesting the putative primary cases [25], whereas more advanced technologies, such as tools based on epigenetic tumor profiling [31] or gene expression analysis [32], can be applied to more enigmatic cases.…”
Section: Methodsmentioning
confidence: 99%